(untitled) (American Journal of Islam and Society, 2006)
The work under consideration is a clear and concise exposition of the life and thought of Muhammad al-Baqir, the great-grandson of Prophet Muhammad and one of the most influential Shi`i Imams, recognized by both the Isma`ili and Ithna`ashari Shi`ahs. In this revised version of her doctoral dissertation, the author draws on a wide-range of primary sources and a selection of secondary materials in order to provide the reader with a portrait of a central figure in Shi`i Islam, one who can also tell us a great deal about the formative stage of Islamic thought. For this reason, Early Shi`i Thought should be of interest not only to students of Shi`ism, but also to all those concerned with the often complex development of Islamic civilization during its early period. The first chapter, which serves as the introduction, constitutes a brief summary of the lives of the first Shi`i Imams and the succession to the Prophet. Here, the author provides us with a list of the primary sources that she will be using throughout her study. The second chapter, dealing with the imamate before the time of Muhammad al-Baqir, is also an historical overview of the lives of the early Imams and their struggles against both the Umayyads as well as some of their own partisans. Chapter 3 is devoted to al-Baqir’s succession to the imamate and to the divisions among the Shi`ah at that time. Al-Baqir’s quietism is contrasted with the political activism of his half-brother Zayd ibn `Ali and the emerging Zaydi Shi`ah, who were willing to revolt against their rulers ...